Evaluation of Antioxidant, Anti-inflammatory and Antimicrobial Activities of the Leaf Extracts of Luffa cylindrica (Journal of Health Sciences, 2018)
Introduction: Luffa cylindrica have been used traditionally in the treatment and management of several disease conditions. This study aimed to evaluate the antioxidant, anti-inflammatory and antimicrobial properties of leaf extracts of the plant, and identifying some of its phytoconstituents.Methods: The crude ethanol and ethyl acetate extracts were evaluated for antioxidant and anti-inflammatory activities using the 1, 1-diphenyl-2-picryl-hydrazyl (DPPH) and paw-fluid displacement methods, respectively. The extracts were tested for antimicrobial activity using the agar well diffusion and agar dilution methods. The ethyl acetate leaf extract of the plant was further subjected to high-performance liquid chromatography-diode-array detection (HPLC-DAD) analysis for the identification of the bioactive compounds.Results: The ethanol and ethyl acetate extracts of L. cylindrica showed average antioxidant properties at 100 µg/mL, with inhibitions of 53.31% and 54.73% respectively. The ethanol extract displayed significant anti-inflammatory activity at 50 mg/Kg with an inhibition of 31.1% compared to 39.7% recorded for the control (diclofenac). The ethyl acetate extract produced an inhibition of 15%. In the antimicrobial evaluation, the ethanol and ethyl acetate extracts showed moderate antibacterial activity against S. aureus, S. Typhi and B. subtilis. The ethyl acetate extract exhibited considerable antimicrobial activity against the test isolates compared to the ethanol extract. HPLC-DAD analysis of the ethyl acetate extract suggested the presence of two flavonoid compounds - luteolin and apigenin as key components of the leaf extract of L. cylindrica. These compounds are known to possess anti-inflammatory, antioxidant and antimicrobial activities.Conclusions: The results of this study showed that the leaf extracts of L. cylindrica possess antioxidant, anti-inflammatory and antimicrobial properties.